THE ROLE OF TREC AND KREC IN ASSESSING THE IMMUNE STATUS OF NEWBORNS - Sikhayeva , N.; Volodchenko, S.; Kovzel, E.; Kissykova, M.; Morenko, M.; Shnaider, K.; Tortayeva , G.; Sagandykova, Ye. (Eurasian Journal of Applied Biotechnology, 2025)
Newborn screening, based on the quantitative assessment of T-cell receptor excision circles (TREC) and kappa-deleting recombination excision circles (KREC) in dried blood spots, allows for the early diagnosis of various types of primary immunodeficiencies. TREC and KREC are circular DNA, markers of new lymphocyte production, formed during the maturation of T- and B-cells. These DNAs do not possess replication capability and are diluted as a result of cell division, making them useful markers for evaluating the appearance of new lymphocytes. PCR analysis of TREC and KREC enables the precise quantitative measurement of their levels, which is crucial for the diagnosis and treatment of immune diseases related to T- and B-cells. The implementation of TREC and KREC assays into neonatal screening programs facilitates the early detection of immunodeficiencies and the identification of novel genetic defects, thereby expanding early diagnostic capabilities. This review provides a detailed examination of the role of TREC and KREC markers in the diagnosis of immunodeficiencies in newborns. Additionally, it analyzes the global experience of implementing TREC and KREC into national newborn screening programs.